Paroxysmal sympathetic hyperactivity caused by neurosyphilis - Shuko Fujiki; Masaki Fujino; Akira Machida (BMJ Neurology Open)
Background Paroxysmal sympathetic hyperactivity (PSH) is a condition characterised by dysregulation of the autonomic nervous system commonly associated with severe traumatic brain injury. Recently, non-traumatic causes, such as infections and autoimmune conditions, have also been reported as potential triggers.Case presentation A 30-year-old man presented with convulsions following 5 days of soliloquy, insomnia and agitation. Neurosyphilis was diagnosed based on elevated non-treponemal and treponemal test findings in the serum and cerebrospinal fluid. Intravenous penicillin administration improved his alertness; however, by day 9, he experienced recurrent episodes of tachycardia, tachypnoea, hyperthermia, hypertension, limb stiffness and diaphoresis. The exclusion of sepsis, pulmonary embolism and malignant syndrome, combined with unremarkable interictal electroencephalogram findings and a high PSH Assessment Measure Score, led to a PSH diagnosis on day 40. Treatment with propranolol, gabapentin and clonidine resolved the episodes, and the patient regained independent ambulation.Conclusions This is the first reported case of neurosyphilis accompanied by PSH. Although PSH is rare in central nervous system infections compared with traumatic brain injury, early recognition is crucial, as untreated cases can persist and result in severe complications.